Exploring the Dynamics of Investment Inflow, Political Institutions, Trade, and Economic Growth: A Developing Countries Perspective (1971-2021) - Zaib, Aurang; Rafique, Maham; Jahanzaib; Gardezi, Muhammad Ali (iRASD Journal of Economics, 2023)
This study delves into the impact of foreign direct investment inflows, political institutions, trade openness, and economic growth within seven developing trade partner nations. Using panel data from 1996 to 2021 and a method called "dynamic fixed effects," our work shows interesting dynamics. FDI has emerged as a potent driver of economic growth with a positive influence. Surprisingly, this study revealed an inverse relationship between trade openness and economic growth. Notably, political institutions’ catalytic role in stimulating both trade and investment inflows further amplifies the economic growth trajectory. These findings provide policymakers with invaluable insights and offer a nuanced perspective on crafting effective sustainable development strategies.